Modus loquendi mysticorum - Širca, Alen Albin (Primerjalna književnost, 2006)
Modus loquendi mysticorum: Mystical Speach and Mystical Poetry. The article attempts to determine the basic characteristics of mystical (Christian) speech on the basis of the mystical theo-logy of Dionysius the Areopagite. As it transpires, the passage from cataphasis to apophasis has the strongest effect in mystical poetry. Conversely, ordinary religious hymns do not include the dynamics of apophatic experiens in their doxological structure.
Keywords: krščanska mistika; mistična teologija; mistično pesništvo; literarne študije